Modeling energy governance index for the adequacy of policy, legal, and institutional response measures for climate compatible development - Iqbal, Kanwar Muhammad Javed; Waheed, Farah; Azhar, Urooj; Akhtar, Nadia; Khan, Muhammad Irfan (Frontiers in Environmental Science, 2022)
Climate compatible and sustainable expansion of energy resources is a major global challenge. Developing countries, with inadequate resources and incoherent policies, and legal and institutional frameworks must strive hard to achieve targets set by the Sustainable Development Goals (SDGs) while keeping track of Nationally Determined Contributions for Greenhouse Gas (GHG) emissions abatement. Inclusive governance is quite complex due to the interplay of informal and formal systems, rules-based to rights-based approaches, and arrangements in national to local scenarios vis-à-vis methodological limitations. In this context, this study aims at developing a governance index for assessing climate compatible development (CCD) by taking case of the energy sector in Pakistan. The study adopted a two-step approach to develop and validate a methodological framework for assessing the adequacy of governance. In the first step, a multivariate analysis model was developed using principle (CP-1), criteria (09), and 43 indicators (PCIs) through stakeholder involvement. In the second step, the model was deployed by combining the Multi Criteria Decision Analysis method with statistical analysis of the dataset. Data were collected from federal and provincial capitals as well as ten districts through a structured scoring matrix consisting of all 43 indicators. The sample population was based on key informant interviews (340), and experts (17) who were engaged through focus group discussion at federal, provincial, and district levels. Respondents were asked to score against each indicator on a ratio scale, which was then aggregated to develop a governance index score. The findings reveal the dearth of a preemptive and comprehensive governance to address climate compatible development in the energy sector in all tiers of constituencies in Pakistan. There is a need for coherent and inclusive policy, and a legal and institutional framework. This study’s outcome authenticates the findings of United Nations SDGs Report 2020 that efforts to achieve sustainable energy targets are not up to scale and stresses the need to speed up the efforts and development of the associated governance framework for renewable energy to achieve climate compatible and SDGs.